Protocolo de cirurgias seguras numa região neotropical no Brasil Central: processo de implantação, avaliação e revisão da literatura - Leite, Giulena Rosa (2017)
Aiming at evaluating the implementation of a safe surgery protocol, developed by the Brazilian National Health Surveillance Agency (ANVISA), an integrative literature review followed by an uncontrolled, quasi-experimental before-and-after intervention study was conducted in public health institutions that possess a surgical center, which are from 5 cities that make up the Southwest Health Region II of the State of Goiás. The review consisted of 19 scientific articles searched by the association of the keywords surgical and checklist and world health organization and implantation. The population was composed of 84 workers from the multiprofessional team before the intervention, 77 workers after the intervention and 680 patients in postoperative period. The data organization process was conducted with Microsoft ® Excel 2010 program and the data analysis was made with the Statistical Package for the Social Sciences (SPSS) program. In order to present the situational diagnosis state of the stages "before training" and "after training" of the professionals, descriptive statistics were used. Then, the comparison of after-training and before-training collected data was performed using the chi-square test to test the significance between proportions. P values <0.05 were considered statistically significant. The female proportion of Healthcare Professionals (PAS) (79.9%) was statistically higher than that of males (20.1%), (p <0.020). The average age was 39.2 (± 9), the predominant age group was 41 years and over (43.9%) and the educational level was less than or equal to twelve years of study (56.1%). Regarding their training, more than a half of them was composed of nursing technicians (77.7%) and worked in a medium-sized hospital (56.8%). Healthcare professionals with a higher academic training level were nurses (8.6%) and medical surgeons or anesthesiologists (13.7%). There was a higher proportion of health professionals who responded positively to the procedures confirmation in step II (98.7%) compared to stage I (67.7%). Likewise, all the items related to visual confirmation and demarcation of the surgical site (1.6% stage I to 97.4% stage II), pulse oximeter presence (82.3% stage I to 98.7% stage II) and verbal review with the anesthesiologists (69.4% stage I to 98.7% in stage II) presented p <0.005. Regarding stage II, “before leaving the surgery room”, the items "compress/instruments count", "surgical specimen identification", "equipment functionality revision" were already performed with great consistency, even before the protocol implementation. Regarding the stage III of the checklist "before leaving the operating room", when we compared the health professionals’ perceptions, before and after the implementation of the checklist, it was observed that the variables "occurrence of wrong procedures notifications”, “the occurrence of surgeries in the wrong patients”, “the occurrence of surgeries in wrong places”, “inadequate antibiotic prophylaxis” and “revision of the postoperative and anesthesia care plan” (p <0.005) were statistically significant (p = 0.000). Conclusion: the level of evidence VI was the one of greater predominance among the articles produced in the period investigated. We interviewed 84 health professionals who work in public surgical centers of RSS II, 90.5% of the female gender; (40.5%), with professional training of Nursing Technicians (82.1%) and schooling less than 12 years of schooling (54.8%). Moments 1 "before the anesthesia" and 2 "before the surgical incision" of the checklist, had a higher rate of adhesion by professionals.